Conducta diagnóstica y terapéutica en el trastorno de déficit de atención e hiperactividad: una actualización. - Toapanta Chimba, Diego Paul (2024)
Attention Deficit Hyperactivity Disorder, or ADHD for short, is a neurodevelopmental disorder characterized clinically by a classic triad of "attention deficit and hyperactivity-impulsivity." ADHD is one of the most prevalent disorders in childhood, often persisting into adolescence and, in some cases, continuing into adulthood. Therefore, a timely and effective diagnosis is crucial, as different forms of pharmacological and non-pharmacological treatments may be employed depending on the patient's developmental stage. The general objective is to update knowledge on diagnostic and therapeutic approaches for patients with attention deficit hyperactivity disorder through a literature review. A non-experimental, descriptive, and cross-sectional basic research was conducted with a qualitative approach. The technique was based on observation to collect relevant information on the topic. The study population consisted of 30 documents, which were reviewed, analyzed, and compiled from the last five years of regional databases such as Scielo and Redalyc and high-impact databases such as PubMed and Elsevier. In addition, textbooks (both physical and digital) and various university platforms were used, all based on inclusion and exclusion criteria. It was identified clinical manifestations specific to this disorder, epidemiological foundation, and clinical diagnostic criteria that enable accurate diagnosis and definitive therapeutic intervention. The conclusion is that attention deficit hyperactivity disorder constitutes a problem in the neurodevelopment of children. Without remission due to misdiagnosis and inadequate treatment, it can impact adolescence and adulthood, affecting the quality of life in terms of health, social, academic, occupational, or emotional aspects. The diagnosis is purely clinical, making the correct use of the medical history essential. Additionally, support from the diagnostic criteria of DSM-5 and ICD-10 is crucial for a definitive diagnosis, allowing for timely non-pharmacological or pharmacological treatment depending on the age and severity of the disorder.